P166 An evaluation of the clinical characteristics of an Anti-SARS-CoV-2 IgG enzyme-linked immunosorbent assay. (11th November 2022) - Moore, J; Robertson, L; Ferguson, T; Cain, E; Goodman, J; Colley, C; Orr, M; Moore, T
Abstract : Introduction and Objectives: The widespread disruption caused by the coronavirus disease 2019 (COVID-19) pandemic continues to impact on daily life. Despite extensive progress in combating the disease, the immunogenic mechanisms are not fully understood. With increasing vaccination rates and the emergence of new variants, it is important to monitor and identify individuals who have produced an immune response and those who remain at higher risk. This study aimed to evaluate the clinical performance of a serological anti-SARS-CoV-2 Immunoglobulin G (IgG) Enzyme-Linked Immunosorbent Assay (ELISA), initially created by AstraZeneca and further developed and validated by ProAxsis Ltd. Methods: The ProAxsis ELISA was used to assess anti-spike protein SARS-CoV-2 IgG levels, in a total of 423 positive plasma samples including asymptomatic, symptomatic, mildly asymptomatic, early infection, post-seroconversion, low and high titre samples and vaccinated individuals. A total of 701 negative plasma samples were also assessed. Samples from each of the SARS-CoV-2 genetic variants (alpha, delta and omicron), along with the World Health Organisation (WHO) International Reference Panel (NIBSC:20/268) were assessed. In addition, 101 plasma samples from patients with antibodies to other coronaviruses or medical conditions were tested. Results: Sensitivity and specificity of the ProAxsis Anti-SARS-CoV-2 IgG ELISA was 100.0% (CI 95% = 99.1 – 100.0%) and 99.3% (CI 95% = 98.3 – 99.8%) respectively. The ProAxsis and comparator test (Euroimmun) demonstrated good agreement, Cohen's Kappa (κ) = 0.991 (CI 95% = 0.982 – 0.999, p<0.0001). Seroconversion was observed with the ProAxsis ELISA at an earlier stage post-infection than with the comparator assay. The WHO Reference Panel was found to correlate perfectly with the Euroimmun assay and were as expected for each titre. Of the 101 virology samples tested only one sample (Anti-malaria plasma P.falciparum ) displayed some cross-reactivity (33.3%). Conclusions: The ProAxsis Anti-SARS-CoV-2 IgG ELISA demonstrated robust clinical performance, with almost perfect agreement against the comparator assay. The ProAxsis ELISA will be highly useful in identifying individuals who have raised antibodies following exposure to SARS-CoV-2 or vaccination and has the potential to play an important role in antibody analyses in clinical trials and large populations. Please refer to page A215 for declarations of interest related to this abstract.